Studi Kelayakan Ekonomi Penggunaan Briket Gambut di Pedesaan Kalimantan Tengah: Economic Feasibility Study Of Peat Briquette Utilization In Rural Central Kalimantan - Danar Ariangga Windra Gautama; Petrisly Perkasa; Christian Novan; Ade Yusuf Ferudyn (Media Ilmiah Teknik Sipil, 2026)
This study aims to analyze the economic feasibility of utilizing peat-based briquettes as an alternative household energy source in rural Central Kalimantan. The research adopts a comparative literature review approach, examining previous studies on peat briquettes, rice husk briquettes, and bagasse briquettes. The analysis focuses on technical parameters (calorific value, moisture content, ash content, burning duration) and economic parameters (production cost, selling price, profit margin, and investment feasibility indicators). The findings indicate that peat briquettes have higher calorific values (5,800–6,200 kcal/g) and longer burning duration (±240 minutes) compared to other biomass fuels. Economically, peat briquettes demonstrate lower production costs (±Rp 3,500/kg), higher profit margins, and positive feasibility indicators, including a positive NPV, BCR of 1.8, and a payback period of approximately two years. Therefore, peat briquettes are economically feasible to be developed as a community-based alternative energy in rural Central Kalimantan, although environmental sustainability must be considered through biomass diversification and regulated peat utilization.